Tindakan Komunikasi Karyawan Muslim di Institusi Katolik di Indonesia: Sebuah Studi tentang Makna Pesan dalam Budaya Organisasi - Yuli Nugraheni; Henri Subiakto; Santi Isnaini (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The study focuses on communication actions and organizational culture that prioritize the meaning of organizational members whose values differ from those of their organization. The study aims to describe the communication actions of Muslim employees due to the meaning of messages in organizational culture in Indonesian Catholic institutions. Using a qualitative approach, an interpretive paradigm, and a phenomenological method. Data collection techniques through interviews and observations. The study's subjects were Muslim employees at four Catholic universities in East Java who met the criteria. The data analysis technique followed the Moustakas sequence. The study's findings on the communication actions of Muslim employees in Catholic institutions are reflected in interactional communication, with adjustments to communicants. Contextual communication actions through the willingness to position themselves, listen, and understand the cultural context. Improvisational communication actions through communication styles with an emotional, flexible, open, and gimmick approach. Episodic communication actions through the participation of Muslim employees in retreat, recollection, and patron day activities. Virtually no previous research has used the model of organizational culture and organizational communication as a cultural performance to examine the experience of multireligious religiosity in religious organizations in the Indonesian context. This research also interprets it using a functional-performative integration framework. This study offers a multidisciplinary approach that bridges organizational culture theory, organizational communication theory, and religious studies—a practice rarely employed in studies of organizational communication in multireligious contexts in Indonesia.